A new approach for studying the dyeability of a multifibers fabric with date pits powders: a specific interest to proteinic fibers. (1st October 2016) - Guesmi, Ahlem; Dhahri, Hajra; Ben Hamadi, Naoufel
Abstract: The use of ecofriendly bio dye has become a matter of significant importance due to the increased environmental awareness. This explains the large number of research developed in this context, especially, when the used dye derived from the waste of a natural product. In the same aims, this study proposes to test the affinity of the dye stuff extracted from the date pits to a Multi-fibers fabric. This choice has been established in order to test the affinity of the extracted coloring matter towards different kinds of fibers. It was shown, that at pH 4, the different kinds of fibers have been dyed. The darker shades have been obtained with wool and silk. Based on those results, they have been selected for developing a dyeing investigation. The effect of the main operating conditions on the dyeing quality resulted has been studied. The dyeing properties were evaluated by measuring K/S and CIELAB values. Fastness properties have been also evaluated, and the overall fastness properties were about 4–5. Interesting fastness properties can be attributed to the metal content in date pits which could act as a bio metallic mordant. Graphical abstract: Highlights: We realize extraction of dyes from date pits powders. We investigate the application of date pits powders in the field of textile. The dyeing conditions and the overall fastness properties were investigated.